Management of gastroesophageal reflux disease in pediatric patients: a literature review - Esposito C; Roberti A; Turrà F; Escolino M; Cerulo M; Settimi A; Farina A; Vecchio P; Di Mezza A (Dove Medical Press, 2015)
Ciro Esposito, Agnese Roberti, Francesco Turrà, Maria Escolino, Mariapina Cerulo, Alessandro Settimi, Alessandra Farina, Pietro Vecchio, Antonio Di Mezza Department of Translational Medical Sciences, Pediatric Surgery, “Federico II” University of Naples, Naples, Italy Abstract: Gastroesophageal reflux (GER), defined as the passage of gastric contents into the esophagus, is a physiologic process that occurs throughout the day in healthy infants and children. Gastroesophageal reflux disease (GERD) occurs when gastric contents flow back into the esophagus and produce symptoms. The most common esophageal symptoms are vomiting and regurgitation. Lifestyle changes are the first-line therapy in both GER and GERD; medications are explicitly indicated only for patients with GERD. Surgical therapies are reserved for children with intractable symptoms or who are at risk for life-threatening complications of GERD. The laparoscopic Nissen antireflux procedure is the gold standard for the treatment of this pathology. A literature search on PubMed and Cochrane Database was conducted with regard to the management of GERD in children to provide a view of state-of-the-art treatment of GERD in pediatrics. Keywords: gastroesophageal reflux, children, medical therapy of GERD, surgical treatment of GERD, laparoscopic Nissen procedure